Performance analysis and prolactin gene variability of Kuttanad ducks of Kerala - Bindya Liz Abraham; Priya Melepat (Journal of Livestock Biodiversity, 2025)
The Kuttanad ducks of Kerala are dual purpose ducks known for their adaptability in different agro-climatic zones of the country. The performance evaluation of Kuttanad ducks in the influenza and flood affected regions of their breeding tract revealed the mean body weight at hatch, at 20, 40, 52 and 72 weeks of age to be 46.34±1.03 g, 1.43 ±1.13 kg, 1.58 ±1.36 kg, 1.65 ±1.54 kg and 1.99 ±1.63 kg respectively. The mean age at first egg, body weight at first egg, egg weight at 40, 52 weeks of age and annual egg production at 72 weeks of age were 139.2 ±2.34 days, 1.43 ±1.13 kg, 60.6 ±2.33 g, 67.5 ±2.12 g and 192.6 eggs respectively. PCR-SSCP and sequence analysis of duck-PRL gene (204 bp exon 5) influencing growth and egg production revealed the locus to be monomorphic and highly conserved in Kuttanad ducks.